Titel prent: De militaire opstanden in Rusland : "Wie het zwaard voert, zal door het zwaard vergaan." - Hahn, Albert,
Titel prent: De militaire opstanden in Rusland : "Wie het zwaard voert, zal door het zwaard vergaan.".